Profil Pasien Karsinoma Hepatoseluler yang Menjalani Terapi Transarterial Chemoembolization (TACE) di RSUD Ulin Banjarmasin Periode 2016-2018 - Muhammad Abdullah Mujahid Fadillah; Mashuri Mashuri; Triawanti Triawanti; Nina Mulyani; Azma Rosida (Homeostasis, 2022)
Abstract: Hepatocellular Carcinoma (HCC) is a malignant tumor attacks hepatocytes. 5.4% of all malignancies in the world caused by HCC. Transarterial chemoembolization (TACE) has been shown to be effective in controlling tumor development and prolonging survival time. This study aims to determine the profile of HCC  patients who were given TACE action at Ulin Hospital Banjarmasin for the 2016-2018 period. descriptive research method using medical record data. The results of the study obtained 29 HCC patients, 62% were aged >50 years; 65,5% gender male; 79,3% Child-Pugh B classification; 62% had liver cirrhosis as a predisposition; 65,5% abdominal pain was the most frequent complaint; 86.2% had radiological imaging; 79,3% ECOG performance value was 2, and 93.1% of patients had no thrombus in the portal vein. Conclusion: HCC patients who were given TACE therapy were the most at the age of >50 years and male gender, Child-Pugh B was the most, the most predisposition to liver disease was liver cirrhosis, the most frequent complaint the feeling is abdominal pain, most radiology imaging there is a typical imaging, the highest ECOG performance value is 2, and most patients do not have a thrombus in the portal vein or inferior vena cava. Keywords: Hepatocellular Carcinoma, TACE, liver cirrhosis Abstrak: Karsinoma Hepatoseluler (KHS) merupakan tumor ganas yang menyerang hepatosit. KHS menyebabkan 5,4% dari keganasan di dunia. Transarterial chemoembolization (TACE) efektif mengendalikan perkembangan tumor dan memperpanjang waktu hidup pada KHS. Penelitian bertujuan mengetahui profil pasien KHS yang mendapat TACE di RSUD Ulin Banjarmasin periode 2016-2018. Metode penelitian deskriptif, menggunakan data rekam medik. Hasil didapatkan 29 pasien KHS, 62% berumur >50 tahun; 65,5% laki-laki; 79,3% klasifikasi child-pugh B ; 62% memiliki sirosis hati sebagai predisposisi; 65,5% nyeri perut menjadi keluhan tersering; 86,2% memiliki gambaran khas radiologi; 79,3% nilai ECOG performance 2, dan 93,1% pasien tidak terdapat trombus pada vena porta. Kesimpulan: pasien KHS yang diberi terapi TACE adalah usia >50 tahun dan laki-laki paling banyak, klasifikasi child-pugh B terbanyak, predisposisi penyakit hati tersering sirosis hati, keluhan tersering nyeri perut, gambaran radiologi terbanyak terdapat gambaran khas, terbanyak nilai ECOG performance 2, dan kebanyakan pasien tidak terdapat trombus di vena porta/vena cava inferior. Kata Kunci: karsinoma hepatoseluler, TACE, sirosis hati